Pengaruh Metode Pembelajaran Learning Strats With A Question terhadap Keterampilan Berbicara pada Pembelajaran Membaca Teks Berita Siswa Kelas VIII Sekolah Menengah Pertama Negeri 13 Seluma - Lestari, Hemi; Suradi, Ahmad; Astuti, Dina Putri Juni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This study aims to determine the effect of the Learning Starts with a Question (LSQ) teaching method on the speaking skills of eighth-grade students at SMP Negeri 13 Seluma. The method used was an experimental study involving verbal reinforcement to enhance students' learning motivation. The research focused on news text learning using the LSQ method to evaluate its impact on students' speaking skills. Data analysis was conducted using statistical tests, showing a t-value of 5.248 compared to a t-table value of 2.042 at a 5% significance level. The results indicate that the Learning Starts with a Question (LSQ) teaching method has a significant effect on students' speaking skills. This is evidenced by the t-value being greater than the t-table value, leading to the acceptance of the working hypothesis stating that the LSQ method influences speaking skills, while the null hypothesis was rejected. In conclusion, the Learning Starts with a Question (LSQ) teaching method significantly contributes to improving students' speaking skills in news text learning and can serve as an effective alternative learning strategy. Keywords: Learning Starts with a Question (LSQ) Method, speaking skills